Inhibiting bacterial secretion systems in the fight against antibiotic resistance. Issue 5 (8th May 2019) - Boudaher, Elizabeth; Shaffer, Carrie L.
Abstract : The search for new ammunition to combat antibiotic resistance has uncovered diverse inhibitors of the bacterial type IV secretion system. Abstract : Antimicrobial resistance is a mounting global health crisis that threatens a resurgence of life-threatening bacterial infections. Despite intensive drug discovery efforts, the rate of antimicrobial resistance outpaces the discovery of new antibiotic agents. One of the major mechanisms driving the rapid propagation of antibiotic resistance is bacterial conjugation mediated by the versatile type IV secretion system (T4SS). The search for therapeutic compounds that prevent the spread of antibiotic resistance via T4SS-dependent mechanisms has identified several promising molecular scaffolds that disrupt resistance determinant dissemination. In this brief review, we highlight the progress and potential of conjugation inhibitors and anti-virulence compounds that target diverse T4SS machineries. These studies provide a solid foundation for the future development of potent, dual-purpose molecular scaffolds that can be used as biochemical tools to probe type IV secretion mechanisms and target bacterial conjugation in clinical settings to prevent the dissemination of antibiotic resistance throughout microbial populations.